(untitled) (2011)
This paper proposes a risk taxonomy that focuses on software acquisition environment. According to this, the goal of this approach is to define an ordered risk classification structure related with to software acquisition. The proposal of a risk taxonomy of software acquisition is motivated by the importance that risks identification activity has and the contribution that a risk taxonomy gives to this activity, because it is known as a technique for effective risks identification, which it's possible to develop a better risk management starting from a better identification of them. This paper includes both the method to construct the taxonomy (called MECT) and the proposed risk taxonomy of software acquisition that was developed.